Evaluating User Satisfaction with Hospital Management Information Systems: A PIECES Framework Analysis at Wates General Hospital - Ferdiana, Ulya Frista; Pramono, Angga Eko (Journal of Intelligent Computing & Health Informatics, 2024)
This study examines the impact of the PIECES framework—Performance, Information, Economics, Control, Efficiency, and Service—on user satisfaction with the Hospital Management Information System (SIMRS) at Wates General Hospital. Despite the hospital's adoption of SIMRS for managing inpatient daily census, issues with data accuracy persist, leading to concerns about system effectiveness and efficiency. Using a cross-sectional design, we collected data from 72 respondents through structured questionnaires and observations. The study employed univariate, bivariate, and multivariate analyses to assess the relationships between the PIECES aspects and user satisfaction. The findings reveal that each PIECES aspect significantly influences user satisfaction, with control and security emerging as dominant factors. Logistic regression analysis indicates that robust control and security measures drastically increase user satisfaction, followed by system performance. Based on these results, we recommend targeted improvements to SIMRS security protocols and system performance to enhance overall user satisfaction. This research contributes to the theoretical understanding of hospital information system evaluation and offers practical recommendations for improving implementation of SIMRS in healthcare settings.